Determination of Elevator Shaft Uprightness Applying the Terrestrial Laser Scanning Method - Kovanič, Ľudovít (GeoScience Engineering, 2013)
This paper presents the results obtained from geodetic measurements and processing the data with the objective to determine geometrical parameters of an elevator shaft applying classical as well as modern approaches for obtaining the measured data. The intention was to verify the possibility to apply the terrestrial laser scanning (TLS) method as a suitable, efficient and precise method for collecting spatial data.